2018
DOI: 10.1063/1.5002532
|View full text |Cite
|
Sign up to set email alerts
|

Defect complexes in Ti-doped sapphire: A first principles study

Abstract: First-principles calculations have been performed to study the formation of defect complexes in Ti doped α-Al2O3 crystals. The formation energies of isolated Ti 3+ and Ti 4+ defects, pairs, triples and quadruples of Ti ions and Al vacancies are computed under different equilibrium conditions of Al-Ti-O related phases. Taking into account charge neutrality of the whole system we determine the equilibrium concentrations of simple and complex defects as well as the total equilibrium concentration of Ti in an α-Al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In this paper we present a thorough investigation of the problem of control of the charge state of titanium in Ti:sapphire. Our investigation compliments the study [14,15] and our recent study [1].…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…In this paper we present a thorough investigation of the problem of control of the charge state of titanium in Ti:sapphire. Our investigation compliments the study [14,15] and our recent study [1].…”
Section: Introductionsupporting
confidence: 76%
“…They differ from ones calculated in Refs. [1,15], where this correction was not taken into account. The concentration of electrically neutral defects depends only on its own formation energy:ñ…”
Section: Equilibrium Concentrations Of Defects In Ti:sapphirementioning
confidence: 99%
See 2 more Smart Citations
“…We again confirmed that Ti segregated at both the type‐I and type‐II grain boundary cores. By referring the Ti‐ L 2,3 edges of Ti 2 O 3 (Ti 3+ ) and TiO 2 (rutile, Ti 4+ ), 39 the valence state of Ti in the type‐I grain boundary core is determined to be 3+, although it has been proposed that the valence state of the Ti doped in α‐Al 2 O 3 single crystal is basically 4+ when the sample is annealed in air 40,41 . Since the valence state of Al is considered to be 3+, the present Ti 3+ substitutes Al site at the type‐I grain boundary core without any Al or O vacancies.…”
Section: Resultsmentioning
confidence: 99%